Pengaruh Model PBL Terhadap Hasil Belajar Siswa Pada Pembelajaran Pendidikan Kewarganegaraan Sekolah Dasar - Oktaviani, Adela; Reinita, Reinita; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to know the effects of using problem based learning toward student learning result of the civic subject for 5th grade students at SDN Bandar Buat. This is a quasi experiment research with non equivalent control group. The population of the research is all 5th grade students of SDN 09 Bandar Buat with class V/A as the treatment class and class V/B as the control class. The research result shows that there is an effect of using PBL model toward students’  learning result of the civic subject for 5th grade students at SDN 09 Bandar Buat. The test result show that 2.488 with P-value 0,016. So, the value achieved is less than α = 0.05. It means that H1 is approved.